Analysis of Financial Decision-Making with a Behavioral Economics Approach: Perspectives on Capital Market Investors - Rizani, Ahmad; Zakariyya Rasyad, Rizky; Budiarti, Lina; Sri Sulistyawati, Upik (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
This study aims to analyze the financial decision-making of investors in capital markets using the approach of behavioral economics. Behavioral economics studies how psychological and emotional factors influence financial decision-making. This study involves analyzing various aspects of investor behavior including loss aversion, information framing, overconfidence, herd behavior, and demographic factors. The results show that investors tend to fear losses more than profits, which affects prudent decision-making. The way information is presented also influences investment decisions, where the formation of a positive or negative frame can affect perceptions of risk and opportunities for profit. Overconfidence also plays a role in investment decision-making, with overconfident investors tend to underestimate risk. Herd behavior is also seen in this study, where investors tend to follow market trends without in-depth analysis, which can increase market volatility. Demographic factors such as age, gender, education, and investment experience also play a role in investment strategy and risk preference. This research provides important insights to investors and market participants about the psychological factors that influence financial decision-making. With a better understanding of investor behavior, it is hoped that investors will be able to make more informed and informed decisions, as well as reduce the impact of psychological biases in the future. financial decision-making in capital markets.